At Europe's end: geographies of Mediterranean crossings. Issue 1 (2nd January 2016) - Linhard, Tabea Alexa
Abstract: Accounts of deadly shipwrecks often lie at the heart of depictions of migration in the Mediterranean, yet these accounts frequently overshadow what happens before and what may happen after tragedies at sea. Stories about clandestine migration cluster around borders on land and sea, producing recurrent images and story lines that reveal the severity of the situation, but not the complexity of lived experience of migration. This article centers on crossings from Africa to Spain along specific routes in order to address this complexity. A close reading of Chus Gutiérrez's film Return to Hansala (2008), in relation to other films and literary texts that also depict the circuitous passage from Africa to Spain, shows that ignoring migratory routes is as thorny as concentrating exclusively on them. Instead, the focus here is on an emotional geography in which the distances between places (continents, towns, shores, ports) are also subjective and constantly evolving.